Pelatihan Manajemen Layanan Digital Dinas Perpustakaan dan Kearsipan Kota Medan dalam Meningkatkan Minat Baca Siswa - Nahar Maganda Saragih; Nur Anzelina Hrp; Sabrina Fitriani (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
Literacy competency is an essential competency for every individual. Good literacy skills can direct individuals to think more wisely, carefully, as well as creatively and innovatively. However, the literacy competence of some people is still not optimal. The aim of implementing this community service is to increase the literacy competency of elementary, middle and high school students in the city of Medan. The number of employees who take part in literacy assistance activities is 30. The assistance method used consists of three stages, namely: planning, implementation and monitoring and evaluation. Planning is carried out by making initial observations through test and non-test activities. Implementation activities are carried out by providing understanding and practice of reading and writing literacy. Monitoring activities are carried out by integrating the participants' competency progress in reading and writing literacy. The mentoring activities that have been carried out can improve the participants' abilities in receptive and productive literacy in the community. The participants were able to reflect on the results of receptive literacy in various creative works as a form of productive competence.